Versatile hysteretic model of reinforcing steel bars with buckling. (January 2023) - Massone, Leonardo M.; Rosa, José; Mesa, Álvaro
Abstract: The buckling of reinforcing steel should be considered in the design of reinforced concrete elements subjected to compression since it can influence the load-carrying capacity and energy dissipation under cyclic loading detrimentally. To capture the influence of buckling in the stress–strain behavior of steel, some models have incorporated geometric and material nonlinearities in the formulation. Others have provided phenomenological curves calibrated with experimental data. Using a lumped plasticity model and sectional analysis based on a fiber model, nonlinearities can be incorporated into the problem. However, solving the equilibrium and compatibility in the nonlinear problem involves complex and inefficient computational methods. In this work, iterations to reach moment equilibrium are avoided by utilizing an expression that relates the average axial strain to the curvature. Cyclic experimental tests collected from the literature, using slenderness values from 6 to 15 and strain range up to 10%, verify the model's accuracy, resulting in prediction errors of the energy enclosed by the hysteretic curves of less than 4% in all cases compared to the iterative model. The results were also consistent with the experimental test results.